Lean Leadership on a Napkin An Executive's Guide to Lean Transformation in Three Proven Steps. - Pilone, Ken (Productivity Press, 2021)
This very concise and straightforward book is aimed at top executives in virtually any industry who are either new to the concept of Lean and its benefits to them or who have stalled in their transformations and are trying to resurrect their momentum. The book is written in a style that mirrors a typical interaction with an executive across a table with a knowledgeable, experienced Lean coach/consultant. Its style and substance reflect what a candid and casual conversation would sound and feel like. The book includes simple hand-drawn images (thus the title Lean Leadership on a Napkin) to facilitate and simplify basic concepts as if a real dialogue was occurring in an informal setting. It assumes that the executives have a little or no previous knowledge of Lean methodologies or Lean Leadership but have awakened to the possibility of their promise to grow themselves and their enterprises dramatically. Most executives have little time for extensive reading or patience with "sales" presentations. Those same leaders will therefore appreciate the simple, uncluttered, and, above all, objective summary this book provides. The book breaks down the process of transforming the organization around Lean principles into three component transformational phases or steps, namely, Introduction, Integration, and Internalization (i.e., the I-3 strategy). Each phase includes critical factors to understand, do, and share as well as deep reflection questions to help leaders decide on an appropriate path forward for themselves as leaders and for their organizations. While the Integration and Internalization steps are introduced here, the primary focus of this work is on those critical issues arising in the early, Introduction, step. A unique advantage of this book is that it braids together four critical elements of success--Lean concepts/methodology, culture change, leadership, and business performance. Essentially, the reader will obtain a broad, basic, and solid understanding and leadership foundation about Lean, the leader's unique role in transformation, and confidence to make appropriate decisions about the how and if to proceed. In addition, it will offer a path forward by providing the reader with abundant resources and consulting support for those seeking to launch a Lean transformation.